Implication of different replicons in the spread of the VIM-1-encoding integron, In110, in Enterobacterales from Czech hospitals - Bitar, Ibrahim; Papagiannitsis, Costas C.; Kraftova, Lucie; Marchetti, Vittoria Mattioni; Petinaki, Efthymia; Finianos, Marc; Chudejova, Katerina; Zemlickova, Helena; Hrabak, Jaroslav (Frontiers in Microbiology, 2023)
Background: VIM metallo-β-lactamases are enzymes characterized by the ability to hydrolyze all β-lactams. Usually, blaVIM-like genes are carried by class 1 integrons. In the Czech Republic, only sporadic cases of VIM-producing Enterobacterales have been reported in which those isolates carried the VIM-1 carbapenemase-encoding integron In110. However, during 2019-2020, an increased number was reported. Therefore, the aim of the current study was to characterize the genetic elements involved in the increased spread of blaVIM genes. Materials and Methods: 32 VIM-producing Enterobacterales collected between 2019-2020 were subjected to: antimicrobial susceptibility testing, integron analysis, and short reads sequencing. Based on the results, nineteen isolates were selected as representative and sequenced using Sequel I platform. Results: The 32 VIM-producing isolates exhibited variations in the MICs of carbapenems. Based on short-read data, 26 of the 32 sequenced isolates harbored the blaVIM-1 allele while six isolates carried the blaVIM-4 gene. The most prevalent was the In110 integron (n=24) and two isolates carried the In4873 class 1 integron. The blaVIM-4 allele was identified in class 1 integrons In1174 (n=3), In416 (n=1), In2143 (n=1) and In2150. Long reads sequencing revealed that the blaVIM was carried by: pKPC-CAV1193-like (n=6), HI1 (pNDM-CIT) (n=4), HI2 (n=3), FIB (pECLA) (n=2) and N (n=1) incompatibility groups. Two blaVIM-carrying plasmids couldn’t be typed by the database, while another one was integrated into the chromosome. Conclusion: We observed the spread of VIM-encoding integrons, mainly of In110, among Enterobacterales isolated from Czech hospitals, but also an increased number of novel elements underlining the ongoing evolution.